Prevalence of orthorexia nervosa: a systematic review and meta-analysis protocol - Julie A Pasco; Lana J Williams; Shae E Quirk; Tayla Eckley; Mariel Messer (BMJ Open)
Introduction Orthorexia nervosa (ON) is a newly recognised condition characterised by an excessive fixation with healthy eating, yet the prevalence of ON is poorly understood. This protocol presents the methodology to undertake a systematic review and meta-analysis on the prevalence of ON in a wide range of populations (including general population and ‘high-risk’). To the authors’ knowledge, the proposed review will be the first systematic review to critically appraise the quality and quantity of evidence on this topic.Methods The protocol has been developed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines. Eligible studies will be identified through a systematic search of electronic databases (eg, Medline Complete, PsycInfo and CINAHL complete via the EBSCOHost platform and Embase). Two reviewers will independently screen and review the full text of records, extract the data and critically appraise the evidence using the Joanna Briggs Institute critical appraisal checklist for prevalence studies. A descriptive synthesis will present the characteristics of the included studies and key findings in text and tables. Where appropriate, meta-analysis will be conducted to determine the proportion of individuals with ON (yes/no) according to population groups of interest (ie, general and ‘high-risk’ populations) and/or ON tools.Ethics and dissemination This review will include published data only; thus, ethical permission will not be necessary. Results of this review will be published in a relevant peer-reviewed scientific journal and presented at conferences in related fields.PROSPERO registration number CRD42024576557.